Response of the sub-tropical ridge of Asia towards an unstable wave of the mid-latitude - THAW, SANHLA (MAUSAM, 1987)
In July .1977, an unstable wave has developed in the mid-latitude. As a consequence, anticyclonic cells formed m the subtropical ridge of Asia. The cells in the mid-troposphere moved west while those m the upper levels moved east. Burma happened to be in the passage of the cells and have experienced change of rainfall pattern.